Improved detection of silent atrial fibrillation using 72-hour holter ECG in patients with ischemic stroke: a prospective multicenter cohort study - Grond, Martin; Jauß, Jan Marek; Hamann, Gerhard; Stark, Erwin; Veltkamp, Roland; Nabavi, Darius; Horn, Markus; Weimar, Christian; Köhrmann, Martin; Wachter, Rolf; Rosin, Ludger; Kirchhof, Paulus (Stroke, 2013)
Background and Purpose—Adequate diagnosis of atrial fibrillation (AF), including paroxysmal AF, is an important part of stroke workup. Prolonged ECG monitoring may improve the detection of paroxysmal, previously undiagnosed AF (unknown AF). Therefore, we evaluated systematic 72-hour Holter ECG monitoring to detect unknown AF for the workup of patients with stroke.Methods—Unselected survivors of a stroke or transient ischemic attack (TIA) without known AF were enrolled in a prospective, multicenter cohort study of 72-hour Holter ECG monitoring in 9 German secondary and tertiary stroke centers between May 2010 and January 2011. In addition to standardized workup of stroke pathogenesis according to the German Stroke Unit protocol, all patients underwent 72-hour Holter ECG monitoring directly after admission. All ECGs were centrally analyzed by 2 independent observers. We determined the proportion of unknown AF and compared the detection rates of 72- and 24-hour monitoring.Results—A total of 1135 patients were enrolled (mean age, 67 years [SD, 13.1 years], 45% women, 29% TIA). Unknown AF was detected in 49 out of 1135 patients (4.3%, [95% confidence interval, 3.4-5.2%]) by 72-hour ECG monitoring. Unknown AF was diagnosed in 29 patients (2.6%) within the first 24 hours of ECG monitoring, and in 20 more patients only by 72 hours of ECG monitoring. The number needed to screen by 72-hour ECG was 55 patients (95% confidence interval [35-123]) for each additional AF diagnosis. Patients with unknown AF were significantly older and had more often a history of previous stroke. Patients with unknown AF were equally distributed within categories of pathogenesis according to Trial of Org 10172 in Acute Stroke Treatment (TOAST) classification.Conclusions—In unselected survivors of stroke or TIA, 72-hour ECG monitoring is feasible and improves the detection rate of silent paroxysmal AF.